TEACHER'S TASKS TOWARDS MEDIA EDUCATION AT SCHOOL - BALAZAK, Marta (Trends in education, 2009)
This article relates to definition of demands towards modern school and modern teacher. These demands are considered towards modern media education. With reference to the features of media society it makes an attempt to define the tasks of teacher and the scope of his/her job.
Keywords: teacher; media; media education; media competence.